Student Perception of Teacher Response to Student Emotion: Associations with Academic Functioning - (:unkn) unknown (My University, 2022)
ABSTRACTSTUDENT PERCEPTION OF TEACHER RESPONSE TO STUDENT EMOTION: ASSOCATIONS WITH ACADEMIC FUNCTIONING by Cassandra M. Matejka The University of Wisconsin-Milwaukee, 2022 Under the Supervision of Professor Dr. Kyongboon Kwon Due to the increased awareness that emotions have on student outcomes within the classroom setting, gaining insight on the emotional socialization process within the classroom setting may lead to continued improvements within the social-emotional learning curricula in the school environment. The goal of this study was to examine the relation between a teacher’s emotion socialization practices and their student’s academic functioning. Specifically, student perceptions of their teacher’s supportive and unsupportive responses were assessed by 398 fourth- and fifth-grade students. I analyzed whether there was a difference in the way students perceived teacher responses to their emotions based on student gender and race. I also analyzed the relation between the students’ perception of their teacher’s response to student emotions and academic functioning. Furthermore, gender and race were analyzed as moderating factors of this relation. The Coping with Children’s Negative Emotions Scale (Fabes et al., 1990) was used to measure student perception of teacher responses to student emotions. The students’ academic functioning was measured using the standardized Forward Exam and teachers reported on the student’s work ethic (Pierce et al., 1999). Data was analyzed using multivariate analysis of variance and hierarchical linear modeling. Results revealed that male students reported teachers used more unsupportive responses to their emotional expression compared to females, Hispanic students reported teachers using less supportive responses compared to White and African American students, and African American students reported that teachers used more unsupportive responses compared to White and Hispanic students. Furthermore, results suggest that students’ perceptions of unsupportive responses by their teacher significantly predicted English language achievement and student work habits. These findings will help close the gap regarding the impact of teacher emotion socialization practices on students’ academic functioning. Implications, limitations, and future directions are discussed. Keywords: emotion socialization, academic functioning, student-teacher relationship, student-perception, unsupportive response to emotion, supportive response to emotion
Keywords: academic functioning; emotion socialization; student-teacher relationship; supportive response to emotion; unsupportive response to emotion